Formação continuada para professores da educação infantil: ações do município de Ivaiporã/PR nos anos de 2021, 2022 e 2023 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This research is the result of an investigation at master's level within the research line "Science Teaching and Mathematics Education" of the Postgraduate Program in Science Teaching and Mathematics Education at the State University of Ponta Grossa. The general objective of this work was to investigate the process of Continuing Education for Early Childhood Education teachers in the Municipality of Ivaiporã/PR in the years 2021, 2022 and 2023. The study consisted of analyzing the actions of 13 Early Childhood Education coordinators, two of whom work at the Municipal Department of Education (SME) and 11 at Municipal Early Childhood Education Centers (CMEIs). In order to gather the information needed for the research, qualitative research strategies were used, including bibliographical, documentary and field research. The empirical research was carried out by consulting documents produced by the City Hall and the Municipal Education Department (SME), as well as through semi-structured interviews. Initially, the interviews were carried out using a Google Forms form and later through scheduled visits. The theoretical framework of the research dialogues with the contributions of authors such as Franco Cambi, Jacques Gélis, Philippe Áries, Moysés Kuhlmann Jr, Lev Semyonovitch Vygotsky, Demerval Saviane, Paulo Freire, Jean Piaget, Francisco Imbernón and Teresa Cristina Rebolho Rego, as well as the official documents that guide the educational system. The results revealed that the Continuing Education process, associated with pedagogical practice, demonstrates the need for Continuing Education to be based on the difficulties encountered in the classroom. One of the main difficulties presented by Early Childhood Education professionals was the process of including people with special needs, especially those linked to Autism Spectrum Disorder (ASD). In addition, the importance of Continuing Education in contextualizing pedagogical practice became evident, with actions and incentives aimed at the needs represented by contemporaneity and which portray educational challenges from Early Childhood Education. The research also took a new look at the challenges of inclusion, highlighting the importance of actions that involve access to social and health care, formalizing multidisciplinary work that contributes significantly to the students' teaching and learning process.
Keywords: Formação Continuada; Educação Infantil; Identidade Profissional Docente; Ação Docente; Continuing education; Early Childhood Education; Professional Teachers' Identity; Teachers' Action; CNPQ::CIENCIAS EXATAS E DA TERRA